Pengaruh Covid-19 dan Volume Perdagangan Terhadap Return Saham - Rousilita Suhendah; Andrew Yonanda (Jurnal Akuntansi, 2022)
This study aims to obtain empirical evidence regarding the effect of COVID-19 and trading volume on stock returns in pharmaceutical and communication companies listed on the Indonesia Stock Exchange in 2020. The independent variable for covid-19 is the number of positive confirmed cases covid-19 and the number of deaths due to COVID-19. Stock trading volume as an independent variable is measured by the natural logarithm of the difference in today's stock trading volume minus yesterday's stock trading volume. Sampling using non-probability sampling with purposive sampling technique. The sample obtained for this study amounted to 24 companies. The results of this research observation indicate that the growth of positive COVID-19 confirmation cases harms stock returns, and trading volume has a positive effect on stock returns. However, the growth of deaths in COVID-19 cases does not affect stock returns. This study implies that the higher the number of positive confirmed cases of COVID-19, the government will carry out bigger distancing social restrictions. The company limits its operations and affects the company's productivity. The company's performance and stock prices have decreased. The higher the trading volume indicates that the company's shares are in demand by investors. Investors respond to market sentiment by buying company shares because investors think that share prices will rise. The increasing stock price has impacted capital gains that will obtain by investors in the futureKeywords: Covid-19, Trading Volume, Stock Return